2021
DOI: 10.3390/su13031380
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Controlled Trial of Forest Bathing Compared with Compassionate Mind Training in the UK: Impacts on Self-Reported Wellbeing and Heart Rate Variability

Abstract: Forest Bathing, where individuals use mindfulness to engage with nature, has been reported to increase heart rate variability and benefit wellbeing. To date, most Forest Bathing studies have been conducted in Asia. Accordingly, this paper reports the first pragmatic controlled trial of Forest Bathing in the United Kingdom, comparing Forest Bathing with a control comprising an established wellbeing intervention also known to increase heart rate variability called Compassionate Mind Training. Sixty-one universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 42 publications
5
61
0
Order By: Relevance
“…Nature-based interventions are potentially cost-effective treatments [6] that can provide multiple benefits [7] and are potentially accessible to a range of people providing there is adequate provision of public greenspace [8]. Forest bathing (shinrin-yoku) has received particular attention because it is often free and more accessible than established health interventions [9]. Other nature-based interventions, including walking in nature, have been demonstrated to have positive wellbeing impacts, including reducing stress levels [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nature-based interventions are potentially cost-effective treatments [6] that can provide multiple benefits [7] and are potentially accessible to a range of people providing there is adequate provision of public greenspace [8]. Forest bathing (shinrin-yoku) has received particular attention because it is often free and more accessible than established health interventions [9]. Other nature-based interventions, including walking in nature, have been demonstrated to have positive wellbeing impacts, including reducing stress levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, as for any therapy, there is still a need to understand how health benefits manifest before nature-based activities could be utilized in practice [12]. A substantial increase in the research base is required before nature-based activities can be prescribed alongside established therapies [9].…”
Section: Introductionmentioning
confidence: 99%
“…Perceptive emotions were used as a gauge to evaluate the psychological responses of participants to experiences in forest settings [16,[23][24][25]. Participants reported that they perceived more positive emotions in a forest environment compared to in urban settings [26]. However, higher self-reported scores that indicated better emotions were sometimes also the result of a maintained emotional state in a forest but a sharp decline of positive emotions in an adjacent promenade [23].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the benefit of NBIs in LTCs is in its infancy, yet recent research comparing forest bathing with compassion mind training in university students found that the interventions had comparable psychological and physiological impacts [ 84 ]. This shows promise since although McEwan and colleagues’ study is one of the first to offer forest-based interventions within the UK, it is a much less familiar intervention within the UK in comparison to its routine embedding in public health in Japan and other Asian countries.…”
Section: Discussionmentioning
confidence: 99%